Interaction and toxicity of ingested nanoparticles on the intestinal barrier. (November 2022) - Stalder, Thomas; Zaiter, Taghrid; El-Basset, Wassim; Cornu, Raphaël; Martin, Hélène; Diab-Assaf, Mona; Béduneau, Arnaud
Abstract: The gastrointestinal tract represents one of primary routes of entry for many nanomaterials. Their size in the nanometer range and their high surface area confer them very interesting properties as food additives. They are used as texturizing, opacifying or anticaking agents. Food packaging contains nanomaterials with antimicrobial properties. Humans are also orally exposed to nanoparticles (NPs) present in the air or drinking water. Ingested NPs can then reach the intestinal lumen and interact with the gastrointestinal fluids, microbiota, mucus layers and the epithelial barrier, allowing a potential translocation. The toxicological profile of ingested NPs is still unclear due to their variety in terms of composition and physicochemical properties as well as the limited number of investigations. Their unique properties related to their small size could however affect the intestinal ecosystem but also the physical and functional properties of the intestinal barrier. This review focuses on the fate of ingested organic and inorganic NPs in the intestinal lumen and their toxicity on the microbiota and epithelial cells. Graphical Abstract: ga1